A HISTORY OF WESTERN EDUCATION AMONG THE KIKUYU, 1898-1952 (1978)
The response of most Kikuyu to Western education was initially negative. This was due In part to the nature of their Indigenous system of education which was intimately related to their political, social and economic set-up, and partly due to their reaction against the initial impact of colonialism on their society. This attitude was abandoned largely as a re stilt of the First World War when colonial demands became intensified and many people were forced to leave their homes to work as carriers. Their experience of meeting others, in camps and during journeys, from societies so such different from their own, suddenly opened up a new world of experience that the indigenous educational precepts could not fully explain or cater for. Their hope after the war that the missionaries would assist then to obtain an education which would enable then to play roles other than serving the white settlers as labourers did not materialise, neither was the government anxious to take over responsibility for African education from the mission societies. This in turn forced the Kikuyu to look for alternative means of securing a type of education which would not be preoccupied with either vocational training or proselytization. The ‘independent’ schools which became widespread in Kikuyu from the 1920s; the 'Githunguri Scheme’; the willingness of the people during the Second World War to devote a substantial amount of money they got through the war to education; the dispute between the AIM and their Kikuyu adherents in Muranga district which led to the establishment of yet another independent educational body; and the rejection of the Beecher Commission on African Education, which in turn led to the closure of all the schools that would not accept its recommendations; were all part of the efforts of the Kikuyu to make their education relevant to the needs of their society.